ANALISIS KOMUNIKASI DAN MOTIVASI KERJA DALAM RANGKA MENINGKATKAN KINERJA KARYAWAN PADA HOLIDAY INN RESORT BARUNA BALI - YANTI, NI PUTU DEVI KUMARA; GEDE, I GUSTI KETUT; SINTADEVI, NI PUTU RITA (Universitas Mahasaraswati K. Mataram, 2024)
This research aims to analyze the influence of communication and work motivation on employee performance at the Holiday Inn Resort Baruna Bali. Data was collected through a survey using a questionnaire filled in by the office employees. The data analysis methods used include correlation analysis, multiple linear regression, coefficient of determination, as well as hypothesis testing using the t test and F test. The research results show that both communication and work motivation partially have a positive and significant influence on employee performance. Simultaneously, communication and work motivation have also been proven to have a positive and significant effect on employee performance, as indicated by the calculated prob.F value (sig.) of 0.000, smaller than the significance level of 0.05 or 5%. Overall, the independent variables, namely communication and work motivation, are able to influence the dependent variable, namely employee performance, with an R square (R2) value of 57.8%. The remaining 42.2% is influenced by other factors outside the variables studied.